Mysticism and Early Analytic Philosophy - Marek Dobrzeniecki (Warszawskie Studia Teologiczne)
Early analytic philosophy is known for its logical rigor that seems to leave no place for non-rational sources of knowledge such as mystical experiences. The following paper shows on the example of Bertrand Russell and Ludwig Wittgenstein that despite of this early analytic philosophy was interested in mysticism and it also shows the roots of this interest. For Russell an application of logical methods to solving philosophical puzzled was an expression of a more fundamental striving – to know the world as it is, sub specie aeternitatis – which is mystical in nature. In turn early Wittgenstein’s philosophy sets the limits of meaningful propositions and provides the distinction between what can be said and what can only be shown and what manifests itself in the world. The latter belongs to the realm of the mystical.